Gaya Bahasa dan Relasi Intertekstual dalam Puisi Marhaban Ya Ramadhan dan Etnik Nusantara - Gustiana; Syofiani Syofiani; Yetty Morelent (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study aims to analyze the use of figurative language and intertextual relationships in the poetry anthology Marhaban Ya Ramadan by Ahmadun Yosi Herfanda and the poetry anthology Etnik Nusantara by Asrizal Nur. This study employed a qualitative descriptive approach using content analysis. The research data consisted of words, phrases, lines, and stanzas in selected poems that indicate the use of figurative language and intertextual relationships. The data sources were the poetry anthologies Marhaban Ya Ramadan and Etnik Nusantara. The analysis was conducted by identifying forms of figurative language, interpreting the meanings constructed through their use, and examining intertextual relationships through the aspects of similarity, transformation, and absorption of textual elements. The findings indicate that figurative language in Marhaban Ya Ramadan is dominated by metaphor, personification, symbolism, repetition, hyperbole, and simile. These forms of figurative language are used to represent spiritual experiences, self-purification, faith, prayer, forgiveness, and reflection on the month of Ramadan. Meanwhile, figurative language in Etnik Nusantara is dominated by personification, metaphor, symbolism, simile, repetition, and hyperbole, which are employed to represent ethnic identity, history, customs, traditions, community life, and the natural richness of the Indonesian archipelago. From an intertextual perspective, Marhaban Ya Ramadan demonstrates strong relationships with Islamic religious texts, particularly the Qur'an, hadith, and Islamic traditions, whereas Etnik Nusantara demonstrates relationships with cultural and historical texts, customs, oral traditions, regional languages, and local wisdom of Indonesian communities. These relationships are manifested through similarities in themes, symbols, imagery, and figurative language, as well as through processes of textual transformation and absorption. The study demonstrates that figurative language functions not only as an aesthetic element but also as a medium for transforming religious and cultural values into literary expressions. Thus, both anthologies demonstrate that poetry serves as a dialogical space connecting literary texts with religion, culture, history, and the collective experiences of society.